Longitudinal study of care needs and behavioural changes in people living with dementia using in-home assessment data - Chloe Walsh; Alexander Capstick; Nan Fletcher-Lloyd; Jessica True; CR&T Group; Ramin Nilforooshan; Payam Barnaghi (Communications Medicine)
Abstract Background People living with dementia often experience changes in independence and daily living, affecting their well-being and quality of life. Behavioural changes correlate with cognitive decline, functional impairment, caregiver distress, and care availability. Methods We use data from a 3-year prospective observational study of 141 people with dementia at home, using the Bristol Activities of Daily Living Scale, Neuropsychiatric Inventory and cognitive assessments, alongside self-reported and healthcare-related data. Results Here we show, psychiatric behavioural symptoms and difficulties in activities of daily living, fluctuate alongside cognitive decline. 677 activities of daily living and 632 psychiatric behaviour questionnaires are available at intervals of 3 months. Clustering shows three severity-based groups. Mild cognitive decline associates with higher caregiver anxiety, while the most severe group interacts more with community services, but less with hospitals. Conclusions We characterise behavioural symptoms and difficulties in activities of daily living in dementia, offering clinically relevant insights not commonly considered in current practice. We provide a holistic overview of participants’ health during their progression of dementia.